2011
DOI: 10.3113/fai.2011.0940
|View full text |Cite
|
Sign up to set email alerts
|

Medium- to Long-Term Outcome of Ankle Arthrodesis

Abstract: Background: Despite improvement in outcome after ankle arthroplasty, fusion of the ankle joint is still considered the gold standard. A matter of concern is deterioration of clinical outcome as a result of loss of motion and advancing degeneration of adjacent joints. We performed a long-term study to address these topics. Methods: Between 1990 and 2005 a total of 121 ankle arthrodeses were performed at our institute. Thirty-five cases were excluded because of simultaneous subtalar arthrodesis. Ten had died and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
117
1
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(134 citation statements)
references
References 30 publications
10
117
1
6
Order By: Relevance
“…Deterioration of the arthritic changes in the subtalar joint was already previously reported in 15 % of patients five years after TAR [23]. At a mean follow up of nine years after arthrodesis, progressive osteoarthritis of the contiguous joints was also appreciated in other studies, however rarely becoming symptomatic in these patients [24]. It has not yet been shown that long-term results after ankle replacement are superior with regard to adjacent joint Values are given as mean ±SD.…”
Section: Discussionmentioning
confidence: 76%
“…Deterioration of the arthritic changes in the subtalar joint was already previously reported in 15 % of patients five years after TAR [23]. At a mean follow up of nine years after arthrodesis, progressive osteoarthritis of the contiguous joints was also appreciated in other studies, however rarely becoming symptomatic in these patients [24]. It has not yet been shown that long-term results after ankle replacement are superior with regard to adjacent joint Values are given as mean ±SD.…”
Section: Discussionmentioning
confidence: 76%
“…In the first 2 years following bilateral TAR, the functional outcome is inferior to that of unilateral TAR. After this point, the difference disappears with mean AOFAS scores at 2 years of 72 (range 54-90) and 75.9 (range 50-96) respectively [5]. Bilateral TAR offers good functional outcome, substantial pain relief [11] and improves all aspects of the SF-36 [14].…”
Section: Discussionmentioning
confidence: 95%
“…Both AA and TAR have been shown to significantly improve overall function [4] and the benefit of unilateral AA in particular can be seen to persist into the medium [5] and up to 20 years post-operatively [6]. However, whilst there is a perceived benefit for TAR [7,8] particularly in those with bilateral ankle OA [7], the evidence supporting the use of TAR over AA is weak and the optimum way to manage those with bilateral ankle OA remains unclear.…”
Section: Introductionmentioning
confidence: 93%
“…), ин-трамедуллярных гвоздей, винтов и пластин, а также вариантами применения костной пластики [12][13][14][15][16]. при этом наиболее частыми причинами неудач яв-ляются несращения и инфекционные осложнения [17][18][19].…”
unclassified